Fast quantitative ROS detection based on dual-color single rare-earth nanoparticle imaging reveals signaling pathway kinetics in living cells. Issue 2 (12th December 2016) - Abdesselem, M.; Ramodiharilafy, R.; Devys, L.; Gacoin, T.; Alexandrou, A.; Bouzigues, C. I.
Abstract : Dual-color single rare-earth nanoparticle imaging enables fast quantitative ROS detection in live cells. Abstract : Reactive oxygen species (ROS), and notably hydrogen peroxide H2 O2, are cellular second messengers that are known to control a variety of signaling processes. They can finely regulate the dynamics of signal transduction, cell response and ultimately tissue function. However, there are very few local, quantitative and time-resolved descriptions of their cellular organization at the scale of molecular reactions, due to the lack of efficient sensors. We thus developed a novel nanoprobe-based ROS detection system using the simultaneous imaging of single lanthanide nanoparticles (YAG:Ce and chemically reduced Gd0.6 Eu0.4 VO4 ). We reveal that both particle luminescence signals are controlled by their H2 O2 local environment. By simultaneously tracking their luminescence, we devised a new approach providing a quantitative (0.5 μM accuracy in the 1–10 μM range) H2 O2 measurement with a 500 ms time resolution, surpassing all existing methods by two orders of magnitude, and revealing previously inaccessible molecular events controlling ROS concentration. We used this nanoprobe in living cells to track fast signaling pathways, by measuring the dynamics of H2 O2 intracellular concentrations, induced by endothelin-1 (ET-1) stimulation. We thus revealed the mechanisms controlling ROS production, notably the activity modulation of the ROS-producing enzyme NADPH oxidase by fast (<10 s) EGFR transactivation, and measured quantitatively their kinetic parameters through a minimal analytical model. Altogether, these results illustrate how lanthanide nanoparticle-based sensors are a powerful tool to dynamically probe molecular mechanisms shaping the oxidative cell response.